URGENSI PERMOHONAN PENETAPAN WALI OLEH ORANG TUA UNTUK PENJUALAN HARTA ANAK PERSPEKTIF UNDANG UNDANG PERLINDUNGAN ANAK - Raden Muyazin Arifin; Hafis Baraas (AL-ASHLAH : Jurnal Hukum Keluarga dan Hukum Islam, 2025)
Minors need the help of guardians to carry out legal acts, including the transaction of children's property. In Indonesian laws, parents have the right to be the guardians of their children and when acting as guardians all the actions they do must be in the best interests of their children. The prominent number of domestic violence against children, especially those committed by parents, deserves attention. Parents have obligations and responsibilities to their children, including child protection. To exercise their rights as guardians, parents must properly fulfill their obligations and responsibilities towards their children. Therefore, the appeal for guardianship through court is important as a means of verification whether parents have properly fulfilled their obligations and responsibilities. In this study, the first core problem is "What is the urgency of appeal for guardianship as the condition for the transaction of children's property from the perspective of the Child Protection Law. This study uses methods of normative juridical, and literature studies with conceptual, case, and statute approaches to examine and discuss the urgency of the appeal for guardianship for the transaction of children's property. The results of the author's research are as follows: the appeal for guardianship for the transaction children's property is important to protect children's rights and so that children are not economically exploited by transaction that is not in their best interests.